The International Insertion of South America: the Unasur Gamble - Chaves García, Carlos (2010)
South American space is currently undergoing a series of transformations that are political, ideological, economic, and social in nature, which point to the development of greater levels of regional autonomy in terms of international insertion. The creation and launch of the Union of South American Nations (Unasur) is the most recent institutional expression of this new attempt at the integration of South American countries, which seeks to articulate the distinct regional agendas proposed by the region’s governments in recent years. In like manner, the new experience of regional cohesion responds to the projection of the geostrategic interests of Argentina, Brazil, and Venezuela, as an expression of the competence of the leadership of said scheme for regional cooperation and integration.